Nonlegal Sanctioning in Private Legal Systems Nonlegal Sanctioning in Private Legal Systems - van Doormaal, Jos (Wirtschaftsrecht und Wirtschaftspolitik, 2021)
Some modern-day trade associations in commodities industries have complex systems of private commercial enforcement. These associations impose nonlegal sanctions on disloyal industry actors for not complying with awards stemming from specialized commercial arbitration after a business conflict. These extrajudicial measures undermine states' rights to enact formal legal rules, and could violate US Antitrust Law and EU Competition Law. Yet, they could be viewed as a viable alternative to lengthy and expensive court litigation. This book provides best practice guidelines to highlight under what conditions nonlegal sanctions imposed by a trade association and executed by its members do not violate US Antitrust Law and EU Competition Law.